Recycling or Sustainability: The Road of Electric Vehicles Toward Sustainable Economy via Blockchain - Katarina Dimic-Misic; Shailesh Singh Chouhan; Vesna Spasojević Brkić; Milica Marceta-Kaninski; Michael Gasik (Recycling)
This semi-systematic review paper discusses four research questions based on findings from the last 10 years: What are the crucial issues in the ongoing debate on the development of the electric vehicle (EV) concept? Where are the major conflicting points and focuses between sustainable economy and EVs? How does the mining of metals and minerals follow current zero-waste sustainability trends, and how does the prediction of the magnitude of the future demand for EV batteries guide strategic decision-making in policies throughout the globe? As it is not easy to currently predict how metals necessary for EV productions will be produced, this article suggests a strategy that is diverse regarding its approaches to shaping the sustainable mining and further development of EVs, along with the involvement of urban planning. Using broad literature and a published pool of prediction scenarios, we provide a comprehensive assessment of future EV battery raw materials development under a range of scenarios, accounting for factors such as developments in battery technology, variations in the EV fleet composition, sustainability aspects of development of second use and recycling technologies. Additionally, this paper demonstrates how blockchain technology is likely to force mineral and metal supply chains to become significantly more traceable and transparent.